Modern Formal Methods and Applications - Gabbar, Hossam A. (Springer Netherlands : Imprint: Springer, 2006)
Formal methods are a robust approach for problem solving. It is based on logic and algebraic methods where problems can be formulated in a way that can help to find an appropriate solution. This book shows the basic concepts of formal methods and highlights modern modifications and enhancements to provide a more robust and efficient problem solving tool. Applications are presented from different disciplines such as engineering where the operation of chemical plants is synthesized using formal methods. Computational biology becomes easier and systematic using formal methods. Also, hardware compilation and systems can be managed using formal methods. This book will be helpful for both beginners and experts to get insights and experience on modern formal methods by viewing real applications from different domains.